Mate-searching context of prey influences the predator–prey space race. Issue 1935 (30th September 2020) - Torsekar, Viraj R.; Thaker, Maria
Abstract : Predation risk is a strong driver of prey distribution and movement. However, fitness-influencing behaviours, such as mating, can alter risk and influence predator–prey space-use dynamics. In tree crickets, Oecanthus henryi, mate searching involves acoustic signalling by immobile males and phonotactic movement by females. Space-use patterns in tree crickets relative to their primary predators, green lynx spiders ( Peucetia viridans ), should therefore depend on their current mate-searching state; whether males are calling or non-calling and whether females are phonotactic or non-phonotactic. We first measured the degree of spatial anchoring of crickets to specific bushes in the field and determined whether that influenced the probability of broad-scale spatial overlap with spiders. In the absence of spiders, all crickets, independent of sex or male calling status, were found to be spatially anchored to specific types of bushes and not uniformly distributed on the landscape. At the broad spatial scale, spiders were more likely to be found on bushes with female crickets and, to a lesser degree, calling male crickets. At a finer spatial scale within a bush, movement strategies of crickets not only varied depending on the presence or absence of a spider, but also on their current mate-searching state. Phonotactic females showed clear predator avoidance, whereas calling and non-calling males moved towards the spider instead of away, similar to predator inspection behaviour seen in many taxa. As the strongly selected sex, males are more likely to undertake risky mate-searching activities, which includes inspection of predator positions. Overall, we found that all crickets were predictably anchored at the landscape scale, but their sex and mate-seeking behaviour influenced the degree of overlap with predators and their antipredator movement strategies. Reproductive strategies within a prey species, therefore, can alter predator–prey space race at multiple spatial scales.